MIDWIFE ASSISTANCE ON THE INDEPENDENCE OF POSTPARTUM MOTHERS CARING THEIR NEWBORNS IN THE MARTAPURA PUBLIC HEALTH CENTER 1 - Bardiati Ulfah; Zaiyidah Fathony; Nelly Mariati (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2021)
Improving maternal and child health has always been a concern every year; it remains a concern throughout the world, various efforts have been made to raise the level to a higher level. The most significant contributor is neonatal mortality; worldwide, in 2015 it was 21 neonatal deaths per 1000 live births. South Kalimantan province accounted for 578 infant deaths in 2018, and Banjar Regency was the third-largest contributor to infant mortality, with 72 deaths. This research used a descriptive method. The sample in this study was 32 postpartum mothers who had newborns from 0-28 days old. Midwife assistance for postpartum mothers caring for newborns is assisted by 93% and unaccompanied by 7%. The mother's independence in performing umbilical cord care is 70% dependent, 15% independent, and 15% total dependence. The mother's independence in bathing the baby is 47% dependent, 40% independent, and total dependence 12%. The mother's independence in breastfeeds their baby is 78% independent, 15% dependent, and 7% total dependence. It is hoped that midwives will continue to provide maximum education and assistance to postpartum mothers to increase mothers' independence in caring for. Keywords: Assistance, Independence, postpartum mothers, newborns